1994
DOI: 10.1007/bf00283432
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis and RFLP mapping of the R1 and R3 alleles conferring race-specific resistance to Phytophthora infestans in progeny of dihaploid potato parents

Abstract: Phytophthora infestans (Mont.) de Bary is the most important fungal pathogen of the potato (Solanum tuberosum). The introduction of major genes for resistance from the wild species S. demissum into potato cultivars is the earliest example of breeding for resistance using wild germplasm in this crop. Eleven resistance alleles (R genes) are known, differing in the recognition of corresponding avirulence alleles of the fungus. The number of R loci, their positions on the genetic map and the allelic relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…A detached leaf assay with P. infestans isolate 90128 revealed 24 resistant and 45 susceptible genotypes, which fits to a 1-2 segregation according to the v 2 test. This segregation is skewed to susceptible, which might be caused by the relatively small population size or by postzygotic selection against unfavourable allelic combinations El-Kharbotly et al 1994). Nine genotypes were not assigned due to unclear observation.…”
Section: Marker-saturated Genetic Linkage Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…A detached leaf assay with P. infestans isolate 90128 revealed 24 resistant and 45 susceptible genotypes, which fits to a 1-2 segregation according to the v 2 test. This segregation is skewed to susceptible, which might be caused by the relatively small population size or by postzygotic selection against unfavourable allelic combinations El-Kharbotly et al 1994). Nine genotypes were not assigned due to unclear observation.…”
Section: Marker-saturated Genetic Linkage Mapmentioning
confidence: 99%
“…Several R genes have been localized, e.g. R1 on chromosome 5 (Leonards-Schippers et al 1992) and R3, R6 and R7 clustered on chromosome 11 (El-Kharbotly et al 1994. R1 and R3 have been isolated (Ballvora et al 2002;Huang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…R2 was localized on chromosome IV (Li et al 1998). Genes R3, R6 and R7 were all mapped to a distal position on chromosome XI (El-Kharbotly et al 1994. Fine mapping of R3 revealed that this resistance is in fact conferred by two closely linked genes R3a and R3b with distinct pathogen speciWcities (Huang et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Soon afterwards, some of them have been introduced into potato cultivars (Niederhauser et al 1954;Stewart and Bradshaw 2001). The Wrst gene for late blight resistance that was mapped and subsequently cloned in potato is R1 on chromosome V ( Leonards-Schippers et al 1994;Ballvora et al 2002). Other R genes originating from S. demissum were mapped to diVerent positions.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, a total of 11 R genes (R1-R11) from Solanum demissum were characterized for potatoes ( Table 2). Most of these R genes, R3 through R11 were mapped to chromosome 11 (Bradshaw et al 2006;El-Kharbotly et al 1994;Huang et al 2004Huang et al , 2005, while R1 (El-Kharbotly et al 1994), R2 (Li et al 2008), and R8 (Jo et al 2011) were mapped to chromosomes 5, 4, and 8, respectively. These R genes were introduced into cultivated varieties worldwide.…”
Section: Genomic Analysis Of Phytophthora Infestansmentioning
confidence: 99%